Research on Transient Characteristics of an Aviation Starter Motor Under Low Temperature and Pressure - Wei Tian; Lin Wang; Xin Bai; Zhiqiang Han; Zinong Zuo; Xueshun Wu; Yi Wu; Yan Yan; Jia Fang (Energies)
To enhance the performance of aviation piston engine starters in high-altitude environments, this study investigated their transient starting characteristics under low-temperature and low-pressure conditions using a high-altitude simulation chamber. Experiments were conducted across ambient temperatures from −60 to 15 °C and pressures from 35 to 95 kPa. The results show that the ambient temperature significantly impacts the transient characteristics of the motor, particularly at the initiation stage, whereas pressure has a weaker effect. For every 5 °C drop in temperature, the peak starting current increases by 1.95 A. From 15 to −60 °C, the maximum difference in the starting current pulse width is 11.64 ms. Furthermore, as the ambient temperature decreases, the average current after the motor stabilizes increases, and the average speed decreases.